2021
DOI: 10.1177/15248380211062221
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care Pathways for Black Persons With Traumatic Brain Injury: A Critical Transdisciplinary Scoping Review of the Clinical Care Journey

Abstract: Objectives: This novel critical transdisciplinary scoping review examined the literature on integrated care pathways that consider Black people living with traumatic brain injury (TBI). The objectives were to (a) summarize the extent, nature, and range of literature on care pathways that consider Black populations, (b) summarize how Blackness, race, and racism are conceptualized in the literature, (c) determine how Black people come to access care pathways, and (d) identify how care pathways in research consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…As noted by strategic approach 1.4, programs for underserved or marginalized populations must be available to address health equity and guarantee universal access to quality healthcare. Additional work focusing on the experiences of underserved, marginalized, or racialized communities, such as the recent critical transdisciplinary scoping review mapping integrated care pathways for Black people experiencing TBI [ 112 ], are needed to ensure integrated care adequately and effectively addresses the needs of these communities.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by strategic approach 1.4, programs for underserved or marginalized populations must be available to address health equity and guarantee universal access to quality healthcare. Additional work focusing on the experiences of underserved, marginalized, or racialized communities, such as the recent critical transdisciplinary scoping review mapping integrated care pathways for Black people experiencing TBI [ 112 ], are needed to ensure integrated care adequately and effectively addresses the needs of these communities.…”
Section: Discussionmentioning
confidence: 99%
“…Very few of the included studies reported on race or ethnicity among study participants and none of the included articles discussed the potential impacts of racism, racialization, or culture, either among survivors or rehabilitation professionals. A recent scoping review investigating integrated care pathways for Black persons reported differential access to and lower quality rehabilitation care for Black people than white people in several included studies ( Omar et al, 2023 ). The authors of studies included in the review discussed systemic inequalities, racial prejudices, and biases as contributors to this differential access, factors that Omar et al (2023) note describe anti-Black racism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review investigating integrated care pathways for Black persons reported differential access to and lower quality rehabilitation care for Black people than white people in several included studies ( Omar et al, 2023 ). The authors of studies included in the review discussed systemic inequalities, racial prejudices, and biases as contributors to this differential access, factors that Omar et al (2023) note describe anti-Black racism. Recognizing, naming, and understanding the impacts of anti-Black, anti-Indigenous, and other forms of racism on IPV survivors seeking rehabilitation are critical to dismantling systems of oppression and providing equitable care.…”
Section: Discussionmentioning
confidence: 99%